First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations Oct. 14th, 1921. *Y.M.C.A., Walthamstow. C.W. SALEEBY, F.R.S.E. "Light Against Death." Oct. 28th, 1921. Y.M.C.A., Walthamstow. Captain REISS. "Housing." Nov. 9th, 1921. Girl Guides, North-West Division. Mrs. M. C. D. WALTERS, C.M.B., M.R.San.I. "Housing and Care of the Home." Nov. 11th, 1921. Y.M.C.A., Walthamstow. Mr. E. FARMER, M.A. "Prevention of Nervous Strain in Industry." Nov. 25th, 1921. Y.M.C.A., Walthamstow. R. STENHOUSE WILLIAMS, M.Sc., L.R.C.P., L.R.C.S., D.P.H. "Milk Supply." Jan. 13th 1922. Y.M.C.A., Walthamstow. R.L.H. McADAM ECCLES, M.S., F.R.C.S. "Great Medical Facts Concerning Alcohol." Jan. 24th, 1922. Co-Operative Women's Guild, Chadwell Heath. Mrs. M. C. D. WALTERS, C.M.B., M.R.San.I. "Housing and Child Welfare." Jan. 30th, 1922. Great Smith Street Evening Institute. OTTO MAY, M.R.C.P. "Causes and Contributing Causes of Physical Disease." March 7th, 1922. Sir John Cass Polytechnic, Aldgate. E.B. TURNER, F.R.C.S. "Recreation and Physical Exercise." March 1st, 8th, 15th, 22nd, 29th, 1922. Infant Welfare Association, Richmond. Mrs. M. C. D. WALTERS, C.M.B., M.R.San.I. "The Healthy Home." March 16th, 1922. Tennyson Street L.C.C. School. Hon. Organiser. "Laws of Health." April 5th, 1922. Pentonville Prison. Sir BRUCE BRUCE-PORTER, K.B.E., C.M.G., M.D. "Some Causes of Disease." EXAMINATIONS May 26th, 1921. Written Examination of Students who attended the Sims Woodhead Constructive Educational Health Lectures Series at MORLEY HALL, George Street, Hanover Square, London. Certificates issued by Medical Council of The People's League of Health and Travelling Scholarship prize awarded to Mrs. M.C.D. Walters, C.M.B, M.R.San.I, Belgium being the country chosen by her for her visit. June 9th, 1921. Oral Examination of same students at League's Headquarters. Examiners: Sir GERMAN WOODHEAD, K.B.E., LL.D., M.D., F.R.C.P. A. D. MARSTON, M.R.C.S., L.R.C.P., L.D.S. F.H. CRIPPS, M.B. MEETINGS ADDRESSED June 16th, 1920. Girls' Friendly Society. Hon. Organiser. "The People's League of Health : Its Aims and Objects." July 8th, 1920. Given-Wilson Institute. Hon. Organiser. "The People's League of Health : Its Aims and Objects." Oct. 25th, 1920. Bristol Rotary Club and Bristol Venture Club. Hon. Organiser. "The People's League of Health : Its Aims and Objects." November, 1920. Hampstead Subscription Library. Hon. Organiser. "The People's League of Health : Its Aims and Objects." Dec. 7th, 1920. Opening of Camden Town Welfare Centre. Hon. Organiser. "The People's League of Health : Its Aims and Objects." Dec. 30th, 1920. Rotary Club, Gosport. Hon. Organiser. "The People's League of Health : Its Aims and Objects." Jan. 18th, 1921. Rotary Club, Glasgow. Hon. Organiser. "The People s League of Health : Its Aims and Objects." Jan. 20th, 1921. Rotary Club, Edinburgh. Hon. Organiser. "The People's League of Health : Its Aims and Objects." Jan. 31st, 1921. Rotary Club, Torquay. Hon. Organiser. "The People's League of Health : Its Aims and Objects." Feb. 4th, 1921. Rotary Club, Gloucester. Hon. Organiser. "The People's League of Health : Its Aims and Objects." Feb. 21st, 1921. Given-Wilson Institute, Plaistow. Hon. Organiser. "The People's League of Health : Its Aims and Objects." March 8th, 1921. Rotary Club, Southend-on-Sea. Hon. Organiser. "The People's League of Health : Its Aims and Objects." March 12th, 1921. Brandlehow Road L.C.C. School, Putney. Hon. Organiser. "The People's League of Health : Its Aims and Objects." 15 200/B/3/2/C693/1/71